E-Tasbyh : Solusi Cerdas Ekonomi Digital Ala Pesantren: Study di Pondok Pesantren Bayt Al-Hikmah - Kurnia, Fitri (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2022)
Based on observations from the interface and questionnaires distributed to users, it is known that one of the supports in making efforts to reduce money losses at the Bayt Al-Hikmah Islamic Boarding School is with provide an interface that is easy to reach and operate. Seeing this background, the authors conducted a research that aims to analyze how effective e-tasbyh as a digital transaction media using fingerprints as the main transaction tool currently beingt implemented at the Bayt Al-Hikmah Islamic Boarding School Pasuruan. The research hypothesis is that e-tasbyh as a digital transaction application at the Bayt Al-Hikmah Islamic Boarding School is effective as a media that helps pesantren in reducing cases of losing money. The things analyzed are about the e-tasbyh interface and the level of effectiveness that are distributed through a quistionnare filled out by 50 respondents from students and 15 respondents from teachers who are currently and have used e-tasbyh in their daily transactions at the Bayt Al-Hikmah Islamic Boarding School. The results of data collection were than processed statistically. From the results of research data processing, it can be concluded that e-tasbyh has proven to be effective to reduce money losses at the Bayt Al-Hikmah Islamic Boarding School. Therefore, the suggestion put forward is that e-tasbyh can be developed again as a media that can be used widely, in an effort to reduce criminal cases, namely money theft.